Factors associated with food choice among long‐term weight loss maintainers. Issue 5 (30th December 2021) - Young, Jacob; Phelan, Suzanne; Alarcon, Noemi; Roake, James; Rethorst, Chad D.; Foster, Gary D.
Abstract: Background: The present study aimed to examine motivations for food choice among long‐term weight loss maintainers (WLM) in a widely used commercial weight management program. Methods: A cross‐sectional study was employed where determinants of food choice were measured in the USA using validated scales: Food Choice Questionnaire, Consideration of Future Consequences, and Eating in the Absence of Hunger. Participants were 3806 WLM following a commercial weight management program (WW International, Inc.) who had maintained a weight loss ≥ 9.1 kg (mean 24.7 kg) for 3.3 years and had a body mass index (BMI) of 27.6 kg m 2 . A control group of weight stable individuals with obesity (controls; n  = 519) had a BMI of 38.9 kg m 2 and a weight change < 2.3 kg over the previous 5 years. Results: WLM vs. controls made food decisions more based on health (18.9 vs. 16.3; η p 2  = 0.052) and weight control (9.9 vs. 7.5; η p 2  = 0.16) and less based on price (8.4 vs. 9.1; η p 2  = 0.10). WLM also scored higher than controls with respect to considering future consequences of behaviours (44.3 vs. 38.4; η p 2  = 0.060) and reported less external eating in the absence of hunger (7.1 vs. 7.5; η p 2  = 0.058). Standard canonical coefficients indicated that making food choices based on weight (0.717) with less value placed on price (−0.33) and greater consideration of future consequences (0.262) contributed independently and most (overall r  = 0.593; p  = 0.0001) to discriminating WLM from controls. Conclusions: In a widely used commercial weight management program, successful WLM reported food decisions based more on weight and less on price and considered future consequences of current behaviours. Abstract : What do weight loss maintainers consider when making food choices? Key points: Long‐term weight loss maintainers consume a diet that is low in calories and micronutrient rich, although the diverse factors that govern these food choices remain unclear. The present study examined diverse factors associated with food choice among weight loss maintainers in a widely used commercial weight management program (WW International, Inc.) compared to weight stable individuals with obesity ("controls"). Weight loss maintainers more than controls made food decisions based on health and weight control and less based on price. Both groups scored similarly in the role of convenience, mood, sensory appeal, natural content, familiarity and ethical concerns. Weight loss maintainers were overall more likely to consider future consequences. In a widely used commercial weight management program (WW International, Inc.), successful weight loss maintainers reported food decisions based more on weight and health and less on price. They also considered future consequences of current behaviours.